The unexplained underperformance syndrome (overtraining syndrome) - Budgett, R. (coachesinfo.com, 2008)
Distinguishing the start of weeks of underperformance and fatigue from normal fatigue in athletes training hard is difficult. It is common for athletes to suffer from a week or two of relative underperformance at times of hard training. Sometimes this underperformance persists for more than two weeks despite adequate rest. Up to 10% of elite endurance athletes per year may suffer from unexplained underperformance syndrome (UUPS).